2011
DOI: 10.1080/01446193.2010.545994
|View full text |Cite
|
Sign up to set email alerts
|

Rethinking prefabricated construction management using the VP‐based IKEA model in Hong Kong

Abstract: Prefabricated construction is regarded by many as an effective and efficient approach to improving construction processes and productivity, ensuring construction quality and reducing time and cost in the construction industry. However, many problems occur with this approach in practice, including higher risk levels and cost or time overruns. In order to solve such problems, it is proposed that the IKEA model of the manufacturing industry and VP technology are introduced into a prefabricated construction proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 78 publications
(46 citation statements)
references
References 30 publications
0
46
0
Order By: Relevance
“…Marasini et al (2001) stated that due to insufficient stockyard space management by stockyard managers and ineffective technologies in selecting suitable locations for product stocks and in tracing them for dispatch, prefabricated elements are often exposed on the yard. Li et al (2011) indicated that safety should be emphasized during the assembly of prefabricated elements because many of these elements are bulky and heavy and can potentially harm the assembly. The defects and obstacles in applying the prefabricated construction method have also been sufficiently addressed in previous research.…”
Section: Background Of Mpcmentioning
confidence: 99%
“…Marasini et al (2001) stated that due to insufficient stockyard space management by stockyard managers and ineffective technologies in selecting suitable locations for product stocks and in tracing them for dispatch, prefabricated elements are often exposed on the yard. Li et al (2011) indicated that safety should be emphasized during the assembly of prefabricated elements because many of these elements are bulky and heavy and can potentially harm the assembly. The defects and obstacles in applying the prefabricated construction method have also been sufficiently addressed in previous research.…”
Section: Background Of Mpcmentioning
confidence: 99%
“…The respondents were from a mix of project participants, with 13.2% from clients/owners, 34.9% from designers, 32.1% from general contractors (including EPC/DB contractors), 15.0% from consultants and 4.7% from subcontractors. Most respondents were senior and professional individuals knowledgeable of BIM use, with 29.2% being project managers or chief project engineers, 17.9% BIM managers, 24.5% BIM engineers, and Integration with schedules and onsite information to manage the storage and procurement processes of project materials and equipments [4,7,35,52] Offsite fabrication Generating digitized information to facilitate greater use of prefabricated components [4,5,35,53,54] the remaining 28.3% being other types of engineers also directly involved in the use of BIM.…”
Section: Sampling and Data Collectionmentioning
confidence: 99%
“…China's prefabricated buildings are still in the initial stage of development, with the prefabrication of components as the main part, and the prefabrication level of factories is generally not high [1,18]. Heng Li proposed the IKEA model of the manufacturing industry and VP technology into a prefabricated construction process [19]. Ting Gong analyzed the application of BIM in different building types and proposed a new mode of combination between BIM technology and the design and production of prefabricated building components [20], but a large number of component data contained in the BIM model are not fully utilized.…”
Section: Research On the Management Of Prefabricated Componentsmentioning
confidence: 99%